1993
DOI: 10.1007/bf00029018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a birch (Betula pendula Roth.) embryogenic gene, BP8

Abstract: We have isolated the birch homologue (BP8) for the carrot embryogenic gene DC8 by heterologous hybridization. The birch BP8 gene encodes a putative protein of 53 kDa, showing 52% sequence identity with the DC8 gene at the amino acid level. The putative BP8 protein contains 20 repeats of 11 amino acids and thus belongs to the group of LEA proteins isolated from such plants as carrot, cotton and wheat. Northern hybridization of mRNA isolated from birch cells representing different stages of somatic embryogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…An exception is the 6th best hit, a late embryogenesis abundant (LEA) protein BP8, from birch (Puupponen-Pimiä et al, 1993). This is a group 3 LEA protein (Pfam LEA_4 family Finn et al, 2008), which is distinct from several other LEA classes.…”
Section: Results Of the Coiled Coil/fourier Transform/composition-basmentioning
confidence: 99%
“…An exception is the 6th best hit, a late embryogenesis abundant (LEA) protein BP8, from birch (Puupponen-Pimiä et al, 1993). This is a group 3 LEA protein (Pfam LEA_4 family Finn et al, 2008), which is distinct from several other LEA classes.…”
Section: Results Of the Coiled Coil/fourier Transform/composition-basmentioning
confidence: 99%
“…This is supported by our other recent studies of ozone-stressed and droughtstressed birch clones (E. Pa$ a$ kko$ nen et al, unpublished) indicating high phenotypic plasticity of leaves and good ability for structural acclimation to reduce water loss, appearing for example as thickened cell walls and smaller leaf size. Extremely low expression level of the BP8 gene during the desiccation phase in the embryogenesis in birch cell cultures has also been reported (Puupponen-Pimia$ et al, 1993).Differential ozone sensitivity of birch clones has previously been reported in several studies by Pa$ a$ kko$ nen et al (1993, 1996, 1997 a). As in the earlier experiments, ozone sensitivity of clone 5 in the present study was indicated by ozone-induced growth reductions, a considerable proportion of visibly injured and yellowed leaves and high induction of genes for PAL and PR-10, occurring the lower stomatal conductance and probable lower ozone uptake by WW ozone plants than by the lessozone-sensitive clone 2.…”
mentioning
confidence: 65%
“…This is supported by our other recent studies of ozone-stressed and droughtstressed birch clones (E. Pa$ a$ kko$ nen et al, unpublished) indicating high phenotypic plasticity of leaves and good ability for structural acclimation to reduce water loss, appearing for example as thickened cell walls and smaller leaf size. Extremely low expression level of the BP8 gene during the desiccation phase in the embryogenesis in birch cell cultures has also been reported (Puupponen-Pimia$ et al, 1993).…”
Section: mentioning
confidence: 85%
See 2 more Smart Citations